1998
DOI: 10.1128/jcm.36.6.1489-1493.1998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performances of Two Commercially Available Tests, a PCR Assay and a Ligase Chain Reaction Test, in Detection of Urogenital Chlamydia trachomatis Infection

Abstract: The diagnostic performance of a PCR test (Roche Cobas Amplicor CT/NG Test) and that of a ligase chain reaction (LCR) test (Abbott LCxChlamydia trachomatis assay) were compared by using endocervical and urethral swab specimen culture as a reference test. First-void urine (FVU) and endocervical and urethral swab specimens were collected from 1,015 unselected patients attending a sexually transmitted disease clinic and a clinic for adolescents in Helsinki, Finland. Chlamydia trachomatis was cultured from samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 26 publications
1
24
2
Order By: Relevance
“…This suggests that young women are the most at risk for Chlamydia and confirms that these individuals are an important target for health education interventions to encourage behavioural changes. Previous studies have shown that diagnosing C. trachomatis infections in women is difficult since, most infections are asymptomatic (13,14). However, in the present study, vaginal discharge, lower abdominal pain, irregular menstruations were significantly associated with C. trachomatis infection in infertile women.…”
Section: Discussioncontrasting
confidence: 54%
“…This suggests that young women are the most at risk for Chlamydia and confirms that these individuals are an important target for health education interventions to encourage behavioural changes. Previous studies have shown that diagnosing C. trachomatis infections in women is difficult since, most infections are asymptomatic (13,14). However, in the present study, vaginal discharge, lower abdominal pain, irregular menstruations were significantly associated with C. trachomatis infection in infertile women.…”
Section: Discussioncontrasting
confidence: 54%
“…Although the diagnosis of chlamydial infection is often made by LCR, urine LCR and cervical LCR are not perfect tests, so we derived their test characteristics from a review of the literature (Table 1). [7][8][9][10][11][12][13] The sensitivity and specificity of urine LE testing in males were derived from the cohort. 5 There were 308 urine specimens evaluated by LE testing in males; 71 (23%) were positive for Chlamydia, of which 21 cases were confirmed by urine LCR.…”
Section: Test Characteristicsmentioning
confidence: 99%
“…In contrast, the prevalence of chlamydia seems to vary widely across and within regions-from below 5 percent to around 25 percent in all regions. have emerged as the standard tests for chlamydia, with sensitivity and specificity better than those from culture (Buimer et al 1996;Gray and Wawer 1996;Puolakkainen et al 1998;Stary et al 1997).…”
Section: Resultsmentioning
confidence: 99%